Leg lymphangioma in an elephantiasis limb - Croci, Fabio; Real, Julio; Belloso, Rogelio; Calleriza, Fernando (Cirugía del Uruguay, 1984)
The authors present a case of lymphangioma set on the leg, with chronic lymphoedema, with fast progressive evolution, in respect of which no surgical action could be attempted. Authors analyze these very seldom found angioformative tumours.